Unpacking the global campaign to delegitimize Israel: Drawing a line between criticism of Israel and denying its legitimacy - Gil David Murciano (Stiftung Wissenschaft und Politik (SWP), 2020)
In the last two decades, international delegitimization of Israel has become a new mode of operation for those denying Israel's right to exist. It encompasses a wide range of civil-society and grassroots organizations.The campaign attempts to imitate the logic of the struggle against the South African apartheid regime - hence to undermine Israel's international legitimacy in a manner that would lead to its isolation and eventually cause it to collapse. In its current phase, the campaign functions as a long-term effort to gradually change the discourse and mindset of Israel's critics in the West. Its main goal is to mainstream delegitimization - hence to reposition anti-Zionism from the radical margins into the mainstream of Western liberal-progressive circles, with specific emphasis on critics of Israel's policies. A key strategy to mainstream delegitimization is to blur the differences between criticism of Israeli policy and challenges to Israel's basic legitimacy. This includes efforts to turn items of the delegitimization agenda into an integral part of the political debate about Israel. As a result, many critics of Israel's policies end up supporting efforts that are led by the delegitimization campaign. The discussion in the West on the Israeli-Palestinian conflict is gradually developing into a dichotomous encounter between supporting Israel and its policies unquestioningly or supporting anti-Zionism. The international delegitimization campaign negates two core principles of European foreign policy. First, it stands in direct contradiction to Europe's core commitment to Israel's right to exist. Second, it promotes rejectionism in Palestinian society as an alternative paradigm to the long-standing European approach of negotiated solution with Israel. The key to confronting delegitimization while providing latitude for criticism is the application of constructive differentiation between criticism of Israel and delegitimization. Critics of Israel should apply responsibility in discourse and action by addressing both their associative context and organizational affiliations with these campaigns of criticism. European civil-society and political actors should differentiate between different types of critics and adjust their engagement policy accordingly.
Keywords: 320